Meta-analysis comparing the efficacy of dobutamine versus milrinone in acute decompensated heart failure and cardiogenic shock. (3rd October 2022) - Bandyopadhyay, D; Malik, A; Goel, A; Biswas, S; Hajra, A; Gupta, R; Lanier, G; Naidu, S
Abstract: Objective: This study aims to evaluate the difference between dobutamine and milrinone in patients presenting with acute decompensated heart failure (AHF). Background: Inotropes are indicated for treating AHF, especially in patients with concomitant hypoperfusion indicative of cardiogenic shock. However, previous studies have not identified the optimal inotrope. We sought to compare outcomes associated with milrinone versus dobutamine in patients with AHF. Methods: A systematic literature search was performed to identify relevant trials from inception to August 2021. Our primary outcome of interest was mortality. Analysis was sub-categorized according to subpopulation, including AHF, AHF with cardiogenic shock (AHF-shock), AHF with a bridge to transplantation (AHF-BTT), and AHF with destination therapy (AHF-DT). Summary effects were calculated using a fixed-effects model as risk ratio or mean difference with 95% confidence intervals for all the clinical endpoints. Results: Ten studies, including one randomized controlled trial with 21, 106 patients, were included in the analysis (4918 patients were in the Milrinone group, while 15188 were in the Dobutamine group). Milrinone was associated with a lower risk of mortality in patients with AHF [relative risk (RR) 0.87; confidence interval (CI):0.79–0.97; p<0.05, heterogeneity I 2 =0%] with event rates of 9.4% vs. 9.8% [number needed to treat (NNT) of 250]. Milrinone was also associated with improved mortality with RR 0.76 (0.79–0.95; p<0.05) in patients with AHF-DT. There was a non-significant trend towards improved mortality in AHF-shock patients. However, AHF-BTT patients had a non-significant trend towards improved mortality with dobutamine. There was no difference between the two strategies for the outcomes of acute kidney injury, initiation of renal replacement therapy, mechanical ventilation, arrhythmias, symptomatic hypotension, and length of hospital stay (LOS) in the overall population. Intensive care unit (ICU) LOS was lower in AHF-shock patients in the milrinone group, whereas dobutamine was associated with a lower length of ICU stay in AHF patients. Conclusion: The cumulative data comparing milrinone with dobutamine indicate an overall marginal benefit of milrinone compared to dobutamine in the totality of patients with AFH with or without cardiogenic shock, and whether or not they are bridged to transplantation or destination assist device. More appropriately powered prospective studies are needed to identify a conclusive benefit of one inotrope over another. Funding Acknowledgement: Type of funding sources: None.